Kineticcharacterizationandmodelingofamicroalgaeconsortium isolatedfromlandfillleachateunderahighCO2 concentrationinabubble columnphotobioreactor (2019)
Background: Thedeterminationofkineticparametersandthedevelopmentofmathematicalmodelsareofgreat interesttopredictthegrowthofmicroalgae,theconsumptionofsubstrateandthedesignofphotobioreactors focusedonCO2 capture.However,mostofthemodelsintheliteraturehavebeendevelopedforCO2 concentrationsbelow10%. Results: A nonaxenicmicroalgalconsortiumwasisolatedfromlandfill leachateinordertostudyitskinetic behaviorusingadynamicmodel.ThemodelconsideredtheCO2 masstransferfromthegasphasetotheliquid phaseandtheeffectoflightintensity,assimilatednitrogenconcentration,ammoniumconcentrationand nitrateconcentration.Theproposedmathematicalmodelwasadjustedwith13kineticparametersand validatedwithagood fit obtainedbetweenexperimentalandsimulateddata. Conclusions: Goodresultswereobtained,demonstratingtherobustnessoftheproposedmodel.Theassumption inthemodelofDICinhibitionintheammoniumandnitrateuptakeswascorrect,sothisaspectshouldbe consideredwhenevaluatingthekineticswithmicroalgaewithhighinletCO2 concentrations.